ENVIRONMENTAL IMPACT OF SEMI-INTENSIVE SWAMP BUFFALO (Bubalus bubalis) FARMING: A CASE STUDY IN SUNGAI BAUNG VILLAGE, RAWAS ULU DISTRICT, NORTH MUSI RAWAS REGENCY - Dori Nuringgani Pratama; John Bimasri; Holidi (Journal of Animal Research and Applied Science, 2026)
This study aimed to evaluate the environmental implications of semi-intensive swamp buffalo (Bubalus Bubalis) farming in Sungai Baung Village, Rawas Ulu District, North Musi Rawas Regency, South Sumatra, Indonesia. The research was conducted from November 2024 to January 2025 using a survey-based descriptive approach. A census method was employed, involving all 30 swamp buffalo farmers operating in the study area. Data were gathered through field observations, structured interviews, questionnaires, and literature review, and subsequently analyzed using descriptive techniques. The findings revealed that 73.3% of respondents practiced a semi-intensive production system. Livestock housing was generally situated 10–20 m from residential areas, while 60.0% of farmers accumulated manure around barns without further treatment and only 40.0% utilized manure as organic fertilizer. These management practices suggest potential environmental concerns associated with waste accumulation, odor generation, and the possible contamination of nearby soil and water resources. Furthermore, the close proximity of livestock housing to residential settlements may increase the likelihood of community exposure to environmental pollutants generated by farming activities. The study concludes that swamp buffalo production in Sungai Baung Village is predominantly managed under a semi-intensive system, with the main environmental management issues related to housing location and limited manure utilization. Therefore, improvements in manure management and housing practices are needed to enhance the environmental sustainability of swamp buffalo farming in the study area.